Inter-relationship between profitability, growth and size: A case of non-financial companies from Pakistan - Rehana Kouser; Tahira Bano; Muhammad Azeem; Masoodl Ul Hassan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
The purpose of this paper is to provide an in-depth description of the inter-relationship between firm size, growth, and profitability of non-financial companies listed at Karachi stock exchange. The study is based on the sample of 70 (seventy) non-financial companies listed at Karachi Stock Exchange of Pakistan, selected on the basis of their market capitalization. Panel data techniques were employed using 700 observations of each of the variables of study; size (log natural of total assets), growth (sustainable growth rate for firm) and profitability (return on assets). Observations are collected for ten years (2001-2010). The study concluded that there is study reveals that all the profitability has strong positive relationship with the growth of the firm; however size has less significant and negative impact on the profitability. One suggestion for further research would be to replicate the study in order to get more cases. Furthermore, it would be valuable to take a more long-term focus to examine the described relationships in the long run. The paper highlights the importance of these measures which are generally used for performance evaluation. Paper sets out the criteria that under which situations the company should focus which of the measure, so that company may derive its strategies on that way. This paper improves our preferences about the three major measures of the firm. Moreover, it contributes to the literature of financial management that how these three measures have trade-off between them.
Keywords: 330; Profitability; Growth; Size; Pakistan